Tinjauan Awal Penyulang Palem di PT. PLN (PERSERO) UIWS2JB UP3 Jambi Menggunakan Software ETAP - Thamrin, Nj.; Suprapto, Eko; P, Hadi (Universitas Batanghari Jambi, 2023)
power flow in an electric power system is an event that flows in the form of active power (P) and reactive power (Q) from a generating system (sending side) through a transmission line or network until it reaches the load side (receiving side). . This power flow analysis has complicated stages if done manually, which requires an ETAP program. ETAP (Electric Transient Analysis Program) is software used to analyze an electric power system. This research was planned in the electrical engineering laboratory, Faculty of Engineering, Batanghari University, while the data was obtained from PT PLN (Persero) UIWS2JB Jambi. The ETAP method can simplify the calculation of the power flow in the palm feeder at PT PLN (Persero) Jambi.